2014
DOI: 10.21765/pprjournal.219196
|View full text |Cite
|
Sign up to set email alerts
|

Serum Selenium and Copper Levels in Children with Simple Febrile Seizure and Viral Infections

Abstract: ÖZETAmaç: Sağlıklı bir sinir sistemi için eser elementler son derece önemlidir. Eser elementlerin düzeyi viral enfeksiyonlar ve ateşli nöbetler sırasında değişiklik gösterir. Bu çalışmanın amacı febril nöbet ve viral enfeksiyonu olan çocukların serum selenyum ve bakır düzeylerini belirlemektir.Gereç yöntem: Basit febril konvülziyon geçiren ve viral enfeksiyonu saptanan 40 çocuk çalışmaya alındı. Kontrol grubu olarak ise ateşi ve viral enfeksiyonu olup nöbet geçirmeyen 40 çocuk seçildi. Her iki gruptan alınan s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…On the contrary; no significant change in the serum Cu level was found in patients with FS in the other studies (12,21) . Balci and Yılmaz (13) showed no significant difference in the serum Cu levels between the SFS group and the control group. Also, Aly et al (22) found that the median serum Cu level in cases with febrile convulsions was non significantly higher than in controls.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…On the contrary; no significant change in the serum Cu level was found in patients with FS in the other studies (12,21) . Balci and Yılmaz (13) showed no significant difference in the serum Cu levels between the SFS group and the control group. Also, Aly et al (22) found that the median serum Cu level in cases with febrile convulsions was non significantly higher than in controls.…”
Section: Discussionmentioning
confidence: 90%
“…Cu is an important element for the function of the nervous system (NS) as Cu is important for normal brain development. Many researchers found that deficiency and excess may cause NS complications and convulsions (11)(12)(13)(14) . There is few published research on the level of cupper in SFS and few compare it to febrile illness with no seizures.…”
Section: Introductionmentioning
confidence: 99%
“…This is similar to a study done by Balci O and Yelmaz D, which also showed no significant co-relation. 9 Production of reactive oxygen species and neuronal damage is one of the hypotheses postulated for causation of febrile seizures in selenium deficient children. Results of the present study indicate a significant correlation between selenium deficiency and febrile seizures.…”
Section: Discussionmentioning
confidence: 99%